2014
DOI: 10.1007/s12088-014-0463-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Cryptdin-2 as an Adjunct to Antibiotics from Various Generations Against Salmonella

Abstract: Emerging drug resistance in Salmonella coupled with the recent poor success rate of antibiotic discovery programs of the pharmaceutical industry is a cause for significant concern. It has forced the scientific community to look for alternative new classes of antimicrobial compounds. In this context, combinations of antimicrobial peptides (AMPs) and conventional antibiotics have gained interest owing to their versatile applications. The present study was therefore planned to evaluate the synergistic effects, if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…Interestingly, β-lactamases are not effective against higher generation cephalosporins with an oxyimino side chain such as cefotaxime, ceftazidime, ceftriaxone, or cefepime9. In our previous study, cryptdin-2 was found to have the potential to augment the activity of conventional, second and third generation anti- Salmonella antibiotics, which was evident by in vitro assays10. In continuation to this, here, we report in vivo synergism in dual functionality i.e.…”
supporting
confidence: 81%
“…Interestingly, β-lactamases are not effective against higher generation cephalosporins with an oxyimino side chain such as cefotaxime, ceftazidime, ceftriaxone, or cefepime9. In our previous study, cryptdin-2 was found to have the potential to augment the activity of conventional, second and third generation anti- Salmonella antibiotics, which was evident by in vitro assays10. In continuation to this, here, we report in vivo synergism in dual functionality i.e.…”
supporting
confidence: 81%
“…In other cases, the second component somehow strengthens the action of the first component by facilitating access to the molecular target. This is how antibacterial peptides work, which cause permeabilization of the membrane, which in turn causes the release of antibiotics into the periplasm and cytoplasm of bacterial cells [42,[51][52][53][54][55][56]. It is also known that Staphylococci have an efflux pump, which determines drug resistance to a large extent because it is responsible for removing from cells various types of substances, which are unnecessary for metabolism or harmful to cells [57].…”
Section: Discussionmentioning
confidence: 99%
“…Cryptdins mediate enteric innate immunity, and their absence may contribute to enhanced susceptibility to infection ( 7 , 40 ). Cry-2 can combat infections and augment the activity of conventional antibiotics in vitro and in vivo ( 8 , 9 ). α-defensins may suppress inflammation by controlling the production of interleukin-1β (IL-1β) ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that paneth cells, which are found in the small intestines of mammals, are involved in the mucosal barrier function ( 6 ) by secreting apical granules containing antimicrobial peptides, including α-defensins, which are termed cryptdins in mice ( 7 ). Cry-2 has potent antimicrobial activity against certain microbes, including Escherichia coli and Salmonella typhimurium ( 8 , 9 ). Previous results suggest that luminal bacteria can increase the expression of Cry-2, particularly in the ileum ( 10 ).…”
Section: Introductionmentioning
confidence: 99%